2017
DOI: 10.1039/c7ra06574d
|View full text |Cite
|
Sign up to set email alerts
|

Formation of unusual microphase-separated ultrathin films of poly(vinyl catechol-block-styrene) (PVCa-b-PSt) at the air–water interface by solution casting onto water

Abstract: Formation of ultrathin films of poly(vinyl catechol-block-styrene) (PVCa-b-PSt) at the air–water interface was accomplished by mixing a THF solution with the water phase followed by solvent evaporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In our hands, we have experienced an occasional runaway polymerization. Some examples of poly­(vinylcatechol-styrene) synthesized by free radical polymerization can be found in the literature. , However, these polymerization reactions were only performed on small scales (e.g., 3 g) and yielded low molecular weight polymers under 50 kg mol –1 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our hands, we have experienced an occasional runaway polymerization. Some examples of poly­(vinylcatechol-styrene) synthesized by free radical polymerization can be found in the literature. , However, these polymerization reactions were only performed on small scales (e.g., 3 g) and yielded low molecular weight polymers under 50 kg mol –1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Beyond our lab, several reports have described alternative polymerization reactions for the synthesis of poly­(vinylcatechol-styrene) and obtaining polymers with low polydispersity. Protected catechol monomers have been randomly copolymerized with styrene by free radical polymerization. , Naturally sourced ferulic acid and caffeic acid monomers have been polymerized following RAFT or anionic polymerization (AP) protocols. Poly­(vinylcatechol-styrene) copolymers have also been synthesized showing a monomer gradient behavior, between styrene and 3,4-dihydroxystyrene, within the polymer chains …”
Section: Introductionmentioning
confidence: 99%
“…27 In particular, synthetic polymers with pendant catechol fragments adhere to various surface types, thus mimicking the behavior of catecholcontaining mussel adhesive proteins. 28 Homo-and copolymers made using catechol-containing monomers have been evaluated as adhesives, 29,30 templates for nanoparticle synthesis, 31,32 or matrices for binding metal ions. 33,34 Recently, we reported on the application of a series of vanillin-derived vinyl-and allyl-substituted dimethoxybenzenes (veratroles) as reactive diluents in sustainable thermally curable thermoset compositions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, synthetic polymers with pendant catechol fragments adhere to various surface types, thus mimicking the behavior of catechol-containing mussel adhesive proteins . Homo- and copolymers made using catechol-containing monomers have been evaluated as adhesives, , templates for nanoparticle synthesis, , or matrices for binding metal ions. , …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that selective incorporation of metal salts into the block copolymer domains can enhance the etch contrast resulting a successful pattern transfer. [34][35][36][37][38] For example, Chai et al showed the creation of various metallic nanowires with metal-doped BCP templates. 39 Here, we demonstrate the fabrication of a well-ordered gold nanowire array in a micro-patterned substrate, prepared from a shear-induced self-assembly of BCPs.…”
Section: Introductionmentioning
confidence: 99%